Optimizing choices and sequences in the diagnostic-therapeutic landscape of advanced triple-negative breast cancer: An Italian consensus paper and critical review. (March 2023) - Miglietta, F.; Fabi, A.; Generali, D.; Dieci, M.V.; Arpino, G.; Bianchini, G.; Cinieri, S.; Conte, P.F.; Curigliano, G.; De Laurentis, M.; Del Mastro, L.; De Placido, S.; et al.
Graphical abstract: Highlights: Triple-negative metastatic breast cancer represents a challenging scenario. Besides chemotherapy, several novel agents are now available in clinical practice. A modified Delphi approach was adopted to address high-priority statements. A set of prioritized consensus statements was provided. Relevant/unexpected results and divisive statements were discussed by the Panel. Abstract: Triple-negative (TN) metastatic breast cancer (mBC) represents the most challenging scenario withing mBC framework, and it has been only slightly affected by the tremendous advancements in terms of drug availability and survival prolongation we have witnessed in the last years for advanced disease. However, although chemotherapy still represents the mainstay of TN mBC management, in the past years, several novel effective agents have been developed and made available in the clinical practice setting. Within this framework, a panel composed of a scientific board of 17 internationally recognized breast oncologists and 42 oncologists working within local spoke centers, addressed 26 high-priority statements, including grey areas, regarding the management of TN mBC. A structured methodology based on a modified Delphi approach to administer the survey and the Nominal Group Technique to capture perceptions and preferences on the management of TN mBC within the Italian Oncology community were adopted. The Panel produced a set of prioritized considerations/consensus statements reflecting the Panel position on diagnostic and staging approach, first-line and second-line treatments of PD-L1-positive/germline BRCA (gBRCA) wild-type, PD-L1-positive/gBRCA mutated, PD-L1-negative/gBRCA wild-type and PD-L1-negative/gBRCA mutated TN mBC. The Panel critically and comprehensively discussed the most relevant and/or unexpected results and put forward possible interpretations for statements not reaching the consensus threshold.